Women's Language in Bargaining: A Sociolinguistic Study of Seller-Buyer Interactions in Dinoyo Market - Hotimah, Emah; Putra, Herdana Hikmal Maulana; Mohed, Abdul; Nur Fitria Anggrisia; Putri, Alifa Nathania (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2024)
This study investigates the characteristics of women’s language in market bargaining, revealing how specific communicative features affect buying and selling interactions. These features include the use of polite and non-confrontational language forms, such as hedges and tag questions, which reflect a desire to maintain harmonious social relations. Drawing on Robin Lakoff’s (1975) theory, the study examines how features like hedges, tag questions, and super polite forms are employed by female sellers and buyers during market interactions. The research methods include direct observation and conversation analysis to identify the frequency and context of these language features. The findings indicate that the use of female language traits not only influences the nature of bargaining but also contributes to establishing and maintaining positive social relationships between sellers and buyers. These insights enhance our understanding of communication strategies in economic contexts and underscore the importance of recognizing gender-specific linguistic features in everyday social interactions. Furthermore, the research suggests that a deeper understanding of women’s language traits can provide practical benefits for market participants, aiding in the improvement of their negotiation and marketing skills